Extensive Modulation of the Fecal Metagenome in Children With Crohn's Disease During Exclusive Enteral Nutrition. (December 2015) - Quince, Christopher; Ijaz, Umer Zeeshan; Loman, Nick; Eren, Murat A; Saulnier, Delphine; Russell, Julie; Haig, Sarah J; Calus, Szymon T; Quick, Joshua; Barclay, Andrew; Bertz, Martin; Blaut, Michael; et al.
Abstract : OBJECTIVES: Exploring associations between the gut microbiota and colonic inflammation and assessing sequential changes during exclusive enteral nutrition (EEN) may offer clues into the microbial origins of Crohn's disease (CD). METHODS: Fecal samples ( n =117) were collected from 23 CD and 21 healthy children. From CD children fecal samples were collected before, during EEN, and when patients returned to their habitual diets. Microbiota composition and functional capacity were characterized using sequencing of the 16S rRNA gene and shotgun metagenomics. RESULTS: Microbial diversity was lower in CD than controls before EEN ( P =0.006); differences were observed in 36 genera, 141 operational taxonomic units (OTUs), and 44 oligotypes. During EEN, the microbial diversity of CD children further decreased, and the community structure became even more dissimilar than that of controls. Every 10 days on EEN, 0.6 genus diversity equivalents were lost; 34 genera decreased and one increased during EEN. Fecal calprotectin correlated with 35 OTUs, 14 of which accounted for 78% of its variation. OTUs that correlated positively or negatively with calprotectin decreased during EEN. The microbiota of CD patients had a broader functional capacity than healthy controls, but diversity decreased with EEN. Genes involved in membrane transport, sulfur reduction, and nutrient biosynthesis differed between patients and controls. The abundance of genes involved in biotin ( P =0.005) and thiamine biosynthesis decreased ( P =0.017), whereas those involved in spermidine/putrescine biosynthesis ( P =0.031), or the shikimate pathway ( P =0.058), increased during EEN. CONCLUSIONS: Disease improvement following treatment with EEN is associated with extensive modulation of the gut microbiome.